2014
DOI: 10.1186/1471-2334-14-438
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KIR genes and their HLA ligands in the pathogenesis of leprosy in a hyperendemic population of Rondonópolis, Southern Brazil

Abstract: BackgroundThe objective of this study was to investigate the association between KIR genes and the immunopathogenesis of leprosy.MethodsThe types of KIR and HLA genes were evaluated by PCR-SSOP-Luminex in 408 patients with leprosy and 413 healthy individuals. Statistical analysis was performed using the Chi-square or Fisher’s exact test and stepwise multivariate analysis.ResultsThere was a higher frequency of activating KIR genes (KIR2DS1, 2DS2 and 3DS1) together with their HLA ligands in the tuberculoid (TT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
1
8
2
1
Order By: Relevance
“…Although Jarduli et al (2014) [19] have not found an association of the homozygous KIR2DL2 gene in the presence of the heterozygous HLA-C group C1/C2 ( KIR2DL2 / KIR2DL2/C1/C2 ) with leprosy, our analysis has shown a risk to the clinical form LL compared to the healthy subjects. We also showed that KIR2DL3/KIR2DL3/C1/C1 is strongly increased in BL patients over the contacts, but previous studies in Southern Brazil [20] and the Mid-West [19] did not show a significant association between KIR2DL3/KIR2DL3/C1/C1 and the susceptibility of BL.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Although Jarduli et al (2014) [19] have not found an association of the homozygous KIR2DL2 gene in the presence of the heterozygous HLA-C group C1/C2 ( KIR2DL2 / KIR2DL2/C1/C2 ) with leprosy, our analysis has shown a risk to the clinical form LL compared to the healthy subjects. We also showed that KIR2DL3/KIR2DL3/C1/C1 is strongly increased in BL patients over the contacts, but previous studies in Southern Brazil [20] and the Mid-West [19] did not show a significant association between KIR2DL3/KIR2DL3/C1/C1 and the susceptibility of BL.…”
Section: Discussioncontrasting
confidence: 86%
“…The cytotoxic function of NK cells on target cells is regulated through the balance between activating and inhibitory signals that results from the interaction of KIRs and their HLA class I ligands [15,16]. Thus, it is possible that KIR molecules play a significant role in controlling the immune response during infections, which would explain the associations observed between certain KIR genes and ankylosing spondylitis [17], Chagas disease [18] and leprosy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…KIR receptors of NK cells may contribute to the occurrence of different immunological and clinical responses to the same disease in a specific population [ 16 ]. Several studies have described the participation of KIR (and their ligands) in infectious diseases, such as AIDS [ 17 , 18 ], hepatitis C [ 19 , 20 ], tuberculosis [ 21 , 22 ], leprosy [ 23 , 24 ] and malaria [ 25 , 26 , 27 ]. KIR are also involved in autoimmune and inflammatory diseases such as pemphigus foliaceus, psoriasis, scleroderma, rheumatoid vasculitis and Crohn’s disease [ 28 , 29 , 30 , 31 , 32 ], as well as in many types of cancer [ 33 36 ] and the survival of transplant patients [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher frequency of inhibitory pairs it was present in Borderline patients when compared to the control group, and a higher frequency of activating pairs as compared to the LL group. It was realized multivariate analysis and confirmed the associations and demonstrated that being a female is a protective factor against the development of the disease per se and the more severe clinical form ( 66 ).…”
Section: Response Innate Immune In Leprosymentioning
confidence: 70%